2017
DOI: 10.1007/s11427-017-9081-x
|View full text |Cite
|
Sign up to set email alerts
|

DICER1 mutations in twelve Chinese patients with pleuropulmonary blastoma

Abstract: Our aim is to examine the impact of DICER1 mutations on the pathogenesis of pleuropulmonary blastoma (PPB) by evaluating the mutation frequency and investigating the family history of Chinese patients with PPB. The family histories of 12 children with PPB recruited consecutively were surveyed. Blood samples from patients and their first-degree relatives were tested for DICER1 mutations. Whole-genome sequencing of blood samples and formalin-fixed and paraffin-embedded (FFPE) tumor tissue was performed in one fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In our series, novel heterozygous germline DICER1 frameshift mutations were found in cases 2 and 3; while a heterozygous germline nonsense mutation, reported recently in another Chinese patient, was detected in Case 4 (Fig 4). 4 The findings of our case series add to the spectrum of known DICER1 mutations, especially to the very limited data from Asia. 4 Diagnosing DICER1 syndrome facilitates surveillance of associated morbidities, familial testing and reproductive counselling for both probands and symptomatic carriers.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In our series, novel heterozygous germline DICER1 frameshift mutations were found in cases 2 and 3; while a heterozygous germline nonsense mutation, reported recently in another Chinese patient, was detected in Case 4 (Fig 4). 4 The findings of our case series add to the spectrum of known DICER1 mutations, especially to the very limited data from Asia. 4 Diagnosing DICER1 syndrome facilitates surveillance of associated morbidities, familial testing and reproductive counselling for both probands and symptomatic carriers.…”
Section: Discussionmentioning
confidence: 56%
“…4 The findings of our case series add to the spectrum of known DICER1 mutations, especially to the very limited data from Asia. 4 Diagnosing DICER1 syndrome facilitates surveillance of associated morbidities, familial testing and reproductive counselling for both probands and symptomatic carriers. 5 Further studies and consideration of a prospective patient registry to define the prevalence of DICER1-associated conditions in both paediatric and adult populations in Hong Kong are warranted.…”
Section: Discussionmentioning
confidence: 56%
“…As our previous study reported, wholegenome sequencing of blood samples identified 6,361, 526 germline variants in this family (her mother and her sister), including the mutation identified by targeted sequencing (c.C3675A). In addition, the tumour tissue of Twin1 and Twin2 harboured a nonsynonymous variant of DICER1 (c.G5125A) [15]. However, no DICER1 mutations were found in Case 2 in the peripheral blood samples of either twin or their mother.…”
Section: Discussionmentioning
confidence: 94%
“…Many PPBs may initially manifest as pulmonary multilocular cysts with subsequent progression . This malignancy is highly aggressive, and types II and III grow rapidly. The pathology of PPB is a dynamic continuum.…”
Section: Discussionmentioning
confidence: 99%